2022
DOI: 10.1055/a-1792-7169
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylation of Paraconic Acids by a Silver(I) Nitrate/Persulfate Combination: An Entry to β-Nitro- and β-Hydroxy γ-Butyrolactones

Abstract: Decarboxylative transformations of paraconic acids, a class of γ-butyrolactones containing a carboxylic acid group at the β position as their characteristic functionality, using a combination of AgNO3/K2S2O8 was investigated. The dual function of AgNO3 as an initiator for decarboxylation process and a nitrogen dioxide radical source that reacts with aliphatic carboxylic substrates of this study was reported for the first time. Starting from paraconic acids, β-nitro- and β-hydroxy γ-butyrolactones were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The final cross-coupling product would be generated via nucleophilic attack. In 2022, the Soorukram group reported that the combined AgNO 3 /K 2 S 2 O 8 system can be used for radical decarboxylative transformations of paraconic acids (Scheme 9) [51]. Under oxidative conditions, a range of paraconic acids can be used as the substrates, and a mixture of β-nitro and β-hydroxy γ-butyrolactones was produced.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final cross-coupling product would be generated via nucleophilic attack. In 2022, the Soorukram group reported that the combined AgNO 3 /K 2 S 2 O 8 system can be used for radical decarboxylative transformations of paraconic acids (Scheme 9) [51]. Under oxidative conditions, a range of paraconic acids can be used as the substrates, and a mixture of β-nitro and β-hydroxy γ-butyrolactones was produced.…”
Section: Methodsmentioning
confidence: 99%
“… AgNO 3 /K 2 S 2 O 8 –mediated radical decarboxylative transformations of paraconic acids (Soorukram et al, 2022 [ 51 ]). …”
Section: Schemesmentioning
confidence: 99%